Photography in Latin America : images and identities across time and space - Cánepa Koch, Gisela, 1964-; Kummels, Ingrid (Postcolonial studies, 2016)
Historical photographs taken in Latin America have now become key sites for memory politics, ethnographic imagination, and the negotiation of identity. This volume opens up a set of questions relating to the contemporaneous agency of images as well as their current appropriation via new technologies. Case studies of pictures taken in Mexico, Columbia, Peru and Brazil analyze these processes by tracing how the images have been resignified over time and space. The contributions examine photographs that have been recently rediscovered by such diverse actors as European museums, human rights organizations, anthropologists, shamans, local historians, and communities of internet users.